Reconfigurable modified wilkinson power divider using PIN diode switch - N. Edward; N. A. Shairi; A. Othman; Z. Zakaria; I. D. Saiful Bahri (Institute of Advanced Engineering and Science, 2020)
In this paper, a reconfigurable modified Wilkinson Power Divider (WPD) was proposed. The operating frequencies of the proposed design were either at 2.5 GHz or 3.5 GHz for Worldwide Interoperability for Microwave Access (WiMAX) applications. This proposed design is reconfigurable in terms of its operating frequency by using PIN diode switches. PIN diode switch was used in this design to reconfigure the microstrip line length. By varying the bias voltage of the PIN diode to +5 V or -5 V, the proposed modified WPD can either operate at 2.5 GHz or 3.5 GHz. Rogers RO4350 (er=3.48, h=0.508 mm) was chosen as the substrate material and copper (thickness=0.035 mm) related to patch of design. Based on simulation results obtained from the Advanced Design System (ADS) software, the modified WPD shows good S-parameter performances at 2.5 GHz and 3.5 GHz. However, the measurement results exhibit frequency shifted. Even though there is a correlation between measurement results and simulation results, the resonant frequency was shifted due to parasitic reactance of the PIN diode.